Qsar Study Of 1,10-Phenanthroline Derivatives As The Antimalarial Compounds Using Electronic Descriptors Based On Semiempirical Am1 Calculation = Kajian QSAR Senyawa Antimalaria Turunan 1,10-Fenantrolin Menggunakan... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Quantitative Structure-Activity Relationship (QSAR) analysis of 1,10-phenantroline analogs as antimalarial drug has been conducted using atomic net charges (q) as predictors of their activity. Data of predictors are obtained from computational chemistry method using semi-empirical molecular orbital AM1 calculation. Antimalarial activities are taken as the activity of the drugs against plasmodium falciparum (FcM29-Cameroun) strain and are presented as the value of In(1/1050) where /C50 is an effective concentration inhibiting 50 % of the parasite growth. The results show that there is correlation between antiplasmodial activity and electronic structure as represented by a linear function of activity versus atomic net charges of N1, C7, C10, C14 atoms on the 1,10-phenanthroline skeleton and is expressed by : log IC50 = -3,4398 â 14,9050 qAli â 8,5589 qCio â 14,7565 qC7 + 5,0457 qCii The equation is significant at 95% level with statistical parameters : n = 13